A histopathological description of Amblyomma sculptum attachment site on the skin of a mare at different moments - Nogueira, Bárbara Cristina Félix; Ervilha, Luiz Otávio Guimarães; Cassiano, Liara de Azevedo; Campos, Artur Kanadani (Archives of Veterinary Science, 2022)
Ticks’ saliva presents immunomodulatory activity and cause several tissue changes at the attachment site on the host’s skin. Here, we compare different moments of the skin of a Mangalarga Marchador mare before, during and after tick attachment. On the skin with a fixed tick, we observed inflammatory infiltrate, degranulated mast cells, areas with an absence of nucleus and presence of pyknotic nuclei, type I collagen bundles are quite thick around the tick’s hypostome, fibrotic process, and the occurrence of cell death by necrosis. In the skin after the tick detached, we observed a complete loss of the structure of the extracellular matrix due to the formation of edema of the inflammatory exudate, a large presence of eosinophils and macrophages, new blood vessels, and dilated vessels, indicating that in the absence of immunomodulation promoted by tick saliva, the animal’s organism can start the repair and healing process.